Assessment of the pelagic fish resources in the Southern Black Sea using echo integration and dual-beam processing - STEPNOWSKI, A.; CEMAL GÜCÜ, A.; BINGEL, F. (Archives of Acoustics, 1993)
The paper synthesizes the results of two hydroacoustic surveys on the pelagic fish stocks off the southern (Turkish) Black Sea coast, carried out during the winter seasons '89 and '90. The acoustic data acquisition and processing for estimating surveyed fish populations have been performed using real-time data analysis system, employing an echo integration and "in situ" target strength estimation by dual-beam processing. The results of the surveys are presented in the form of fish density and biomass distribution charts, 3D target strength histograms and reports. These findings provide quantitative measures of fish abundance together with their statistical characteristics and distribution patterns of the surveyed pelagic fish populations.